Management of Fournier's Gangerene : Experience at Nawaz Sharif Social Security Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective: To analyze the results obtained in the Department of Urology, N.S.S.S. Hospital, Lahore presented with Fournier's Gangerene. Method : The charts of 32 patients were reviewed who were diagnosed with Fournier's Gangerene and admitted in Urology Department from January 2002 to December 2011. Frequencies of Age, Diabetes Mellitis, Mortality, Unilateral Orchidectomy, Skin grafting, duration of Hospital stay and time of secondary closure of wound were calculated. Results : All the patients were male with mean age of 53 + 5 years (min. 45 and max. 65 years). Among these 32 patients 2 patients (9.1 %) died due to Extensive disease. The location and extent of injury of all the patients was perineum. Among all 16 patients (50 %) were suffering with uncontrolled Diabetes Mellitis. All patient underwent surgical debridment. The testes of all the patients were burried in thigh anteriorly. Unilateral Orchidectomy was done in 2 patients (9.1 %). The testes of 3 patients (13.6 %) were placed back in scrotum at the time of secondary closure. Skin grafting was done in 3 patients (13.6 %). The mean duration of hospital stay was 17 + 8 days (min. 1 and max. 35 days). The secondary closure of wound was done on 14th + 4 day on an average (min. 7 and max. 24 day). Conclusion : Despite all the current advances in the treatment today, Fournier's Gangerene continues to show high mortality and morbidity rates. Early recognition of infection associated with aggressive and invasive treatment are essential to reduce these prognostic indices.
Keywords: Fournier's gangrene, Necrotizing fasciitis, Surgical infection, Debridement